Polyaniline/attapulgite-supported nanoscale zero-valent iron for the rival removal of azo dyes in aqueous solution - Hui Xu; Yajuan Zhang; Yong Cheng; Weiguo Tian; Zeting Zhao; Jin Tang (Adsorption Science & Technology)
In this paper, polyaniline/attapulgite (PANI/APT)-supported nanoscale zero-valent iron (nZVI) composites were synthesized by liquid-phase chemical reduction method and used for the removal of two kinds of dyes. The structure of as-prepared nZVI/PANI/APT was characterized by various test methods. The removal property and degradation mechanism for azo (alizarin yellow R, methyl red, chrome black T, methyl orange) and non-azo (methylene blue, rhodamine B) dyes in aqueous solution were investigated. The presence of PANI/APT can decrease the aggregation of nZVI particles with maintenance of reactivity and improving adsorption capacity for degradation azo dye. The experiment results showed that the removal property of the composite materials on azo dyes is obviously better than that on non-azo dyes. The varying removal efficiencies of dyes depend on the different degradation mechanisms. Azo dyes removal by nZVI/PANI/APT was mainly due to the reductive cleavage of the N = N of nZVI, while non-azo dyes removal mainly contributes to the adsorption of PANI/APT. The study demonstrated that nZVI/PANI/APT has potential applications for the removal of azo dyes from wastewaters.